Advances in design for cross-cultural activities. Part II - Schmorrow, Dylan D.; Nicholson, Denise, 1967- (Boca Raton, Fla. : CRC Press, 2013)
"This reference focuses on decision-making styles within cultures. It focuses on cooperative, collaborative, avoidant, competitive, and dominant styles of decision making, and discusses how each process is modified by the culture. The contributors examine issues within culture that affect decision making, such as individualism and collectivism, considered the most important influences in decision making. This reference is one of 10 predicted to be derived from the 2012 Applied Human Factors and Ergonomics (AHFE) Conference"--
section 1. Multifarious modeling discussions -- section 2. Verification, validation, and assessment -- section 3. Language, trust, and culture -- section 4. Social media and culture -- section 4. Social science and culture.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Decision making -- Cross-cultural studies; Electronic books